Divanillin-Based Aromatic Amines: Synthesis and Use as Curing Agents for Fully Vanillin-Based Epoxy Thermosets - Savonnet, Etienne; Le Coz, Cedric; Grau, Etienne; Grelier, Stéphane; Defoort, Brigitte; Cramail, Henri (Frontiers in Chemistry, 2019)
Abstract